(3aUhd CHbQGWs - (3GHbQGW GdMcjes ((3YdGA Hf GdMSjf Hf Ydi GdHjgbi s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdfhQ hGdXdGe hHYO aEf CHG GdMSf WGgQ Hf GHQGgje GdSLRi bO HhH aUhd HbQGW GdMcje GdHGH GdChd ajeG bGd ai UOQ GdcdGe hGdCMcGe GdcdjI GdYeQ bUjQ hGdUfGYI WhjdI s
(3BNQgG (B:s
(3aUd aef YQVJ dg ai GdMei GdeMQbI QYTI aEf GNJdW Pgfg jMdgG Yfg JeJ GdaUhd dCHbQGW s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jdjg ahGFO deMeO Hf RcQjG GdQGRis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1267s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs